Effectiveness of the ‘One Week One Egg’ Program in Preventing Stunting in Palangka Raya City - Astoeti, Dileli Dharma; Widiarti, Astri (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2026)
Stunting remains a significant public health issue in Indonesia because its impact not only hinders linear growth but also reduces cognitive development, educational attainment, and long-term productivity. These risks prompted the government to accelerate its eradication through RAN-PASTI 2021–2024. In response, the city of Palangka Raya established a Stunting Reduction Acceleration Team (TPPS) and introduced several innovations, including the One Week One Egg (OWOE) programme, which engages civil servants, students, and contract workers in donating eggs to stunted toddlers and at-risk families. This study aims to evaluate the effectiveness of OWOE in supporting stunting reduction efforts at the city level. The method used is a literature review based on secondary data from government reports, TPPS documents, the Indonesian Nutrition Status Survey (SSGI), and scientific publications on animal-based foods and child nutrition. The evaluation was conducted by analysing participation levels, the number of eggs collected, beneficiary coverage, and its correlation with changes in stunting prevalence. The results show that OWOE successfully collected around 3,250 eggs per week (108 trays) and served 54 toddlers, although this coverage remains far below the total of 7,622 at-risk families. Stunting prevalence in Palangka Raya also decreased significantly from 28% in 2023 to 19.1% in 2024, lower than provincial and national rates, indicating OWOE’s contribution to strengthening convergence efforts. With its simple, low-cost, and community-based approach, OWOE has the potential to be further developed and replicated in other regions to support the achievement of national stunting reduction targets.